Assessing Climate Change Impact on the Spatial Dependence of Extreme Snow Depth Maxima in the French Alps. Issue 10 (16th October 2018) - Nicolet, Gilles; Eckert, Nicolas; Morin, Samuel; Blanchet, Juliette
Abstract: Modeling extreme snow depths in space is important for water storage, tourism industry, mountain ecosystems, collapse of buildings, and avalanche prevention. However, studies modeling the spatial dependence structure of extremes generally assume temporal stationarity which is clearly questionable in a climate change context. We model climatic trends within the spatial dependence structure of extremes, with application to a data set of snow depth winter maxima. From 82 stations spanning the 1970–2012 period in the French Alps, we infer a strong decrease in the range of spatial extremal dependence. This finding is related to a strong decrease in both the snow precipitation ratio and the winter cumulated snowfall, due to increasing temperatures. Hence, we demonstrate that the spatial dependence of extreme snow depths is impacted by climate change in a similar way as has been observed for extreme snowfalls. Furthermore, snow depths maxima are more spatially dependent than snowfalls. The space‐time approach that we introduce may be very useful for assessing past and future evolutions under ongoing climate change in various hydrological quantities. Key Points: The temporal trends in the spatial dependence structure of extreme snow depths are analyzed using max-stable processes The spatial dependence of extreme snow depths in the French Alps shows a strong decrease due to climate change Extreme snow depths are impacted like extreme snowfalls by climate change but they are more spatially dependent